# Is 42 a sum of three cubes?

### Is 42 a sum of three cubes?

"Dr. Andrew Booker, Reader of Pure Mathematics from the University's School of Mathematics, has now discovered the solution for number 33: (8,866,128,975,287,528)³ + (–8,778,405,442,862,239)³ + (–2,736,111,468,807,040)³."

Source:

https://phys.org/news/2019-04-bristol-mathematician-diophantine-puzzle.html
Guest

### Re: Is 42 a sum of three cubes?

Guest wrote:"Dr. Andrew Booker, Reader of Pure Mathematics from the University's School of Mathematics, has now discovered the solution for number 33: (8,866,128,975,287,528)³ + (–8,778,405,442,862,239)³ + (–2,736,111,468,807,040)³."

Source:

https://phys.org/news/2019-04-bristol-mathematician-diophantine-puzzle.html

Since 33 = (8,866,128,975,287,528)³ + (–8,778,405,442,862,239)³ + (–2,736,111,468,807,040)³, we seek the solution of variables, a, b, and c such that

42 = (8,866,128,975,287,528 + a)³ + (–8,778,405,442,862,239 + b )³ + (–2,736,111,468,807,040 + c)³.

Use Newton Method and the link(modify the four variables to three variables):

https://www.math10.com/forum/viewtopic.php?f=63&t=7803&start=20
Guest

### Re: Is 42 a sum of three cubes?

Guest wrote:
Guest wrote:"Dr. Andrew Booker, Reader of Pure Mathematics from the University's School of Mathematics, has now discovered the solution for number 33: (8,866,128,975,287,528)³ + (–8,778,405,442,862,239)³ + (–2,736,111,468,807,040)³."

Source:

https://phys.org/news/2019-04-bristol-mathematician-diophantine-puzzle.html

Since 33 = (8,866,128,975,287,528)³ + (–8,778,405,442,862,239)³ + (–2,736,111,468,807,040)³, we seek the solution of integer variables, a, b, and c such that

42 = (8,866,128,975,287,528 + a)³ + (–8,778,405,442,862,239 + b )³ + (–2,736,111,468,807,040 + c)³.

Use Newton Method and the link(modify the four variables to three variables):

https://www.math10.com/forum/viewtopic.php?f=63&t=7803&start=20

...
You can also solve the Diophantine equation,

$$x^{3}$$+ $$y^{3}$$+ $$z^{3}$$ = 42.

Good luck!
Guest

### Re: Is 42 a sum of three cubes?

What does the graph of $$x^{3}+y^{3}+z^{3}=1$$ look like?

Source:

https://www.quora.com/What-does-the-graph-of-x-3+y-3+z-3-1-look-like
Guest

Guest

### Re: Is 42 a sum of three cubes?

Guest wrote:
Guest wrote:
Guest wrote:"Dr. Andrew Booker, Reader of Pure Mathematics from the University's School of Mathematics, has now discovered the solution for number 33: (8,866,128,975,287,528)³ + (–8,778,405,442,862,239)³ + (–2,736,111,468,807,040)³."

Source:

https://phys.org/news/2019-04-bristol-mathematician-diophantine-puzzle.html

Since 33 = (8,866,128,975,287,528)³ + (–8,778,405,442,862,239)³ + (–2,736,111,468,807,040)³, we seek the solution of integer variables, a, b, and c such that

42 = (8,866,128,975,287,528 + a)³ + (–8,778,405,442,862,239 + b )³ + (–2,736,111,468,807,040 + c)³.

Use Newton Method and the link(modify the four variables to three variables):

https://www.math10.com/forum/viewtopic.php?f=63&t=7803&start=20

...
You can also solve the Diophantine equation,

$$x^{3}$$+ $$y^{3}$$+ $$z^{3}$$ = 42.

Good luck!

If we decide to use the Newton Method to solve our system of three nonlinear equations, our initial vector could be,

[$$x_{0}, y_{0}, z_{0}$$] = [8,866,128,975,287,528, –8,778,405,442,862,239, –2,736,111,468,807,040].

Therefore, we have,

$$n_{10} = y_{0} + z_{0}$$;

$$n_{20} = x_{0} + z_{0}$$;

$$n_{30} = x_{0} + y_{0}$$.

And $$N_{0 }$$= [$$n_{10 }, n_{20}, n_{30}$$].
Guest

### Re: Is 42 a sum of three cubes?

Update:

$$n_{10} = y_{0}^{3} + z_{0}^{3}$$;

$$n_{20} = x_{0}^{3}+ z_{0}^{3}$$;

$$n_{30} = x_{0}^{3}+ y_{0}^{3}$$.
Guest

### Re: Is 42 a sum of three cubes?

Guest wrote:Update:

$$n_{10} = y_{0}^{3} + z_{0}^{3}$$;

$$n_{20} = x_{0}^{3}+ z_{0}^{3}$$;

$$n_{30} = x_{0}^{3}+ y_{0}^{3}$$.

$$x_{k}= (42 - n_{1k})^{1/3}$$;

$$y_{k}= (42 - n_{2k})^{1/3}$$;

$$z_{k}= (42 - n_{3k})^{1/3}$$;

$$N_{k+1} = N_{k} +J_{k}^{-1} * N_{k}$$

where $$N_{k}$$ = [$$n_{1k}, n_{2k}, n_{3k}]$$ (column vector)

and where $$J_{k}^{-1}$$ is inverse of the

Jacobian matrix (3 x 3), $$J_{k}$$...
Guest

### Re: Is 42 a sum of three cubes?

Guest wrote:
Guest wrote:Update:

$$n_{10} = y_{0}^{3} + z_{0}^{3}$$;

$$n_{20} = x_{0}^{3}+ z_{0}^{3}$$;

$$n_{30} = x_{0}^{3}+ y_{0}^{3}$$.

$$x_{k}= (42 - n_{1k})^{1/3}$$;

$$y_{k}= (42 - n_{2k})^{1/3}$$;

$$z_{k}= (42 - n_{3k})^{1/3}$$;

$$N_{k+1} = N_{k} +J_{k}^{-1} * N_{k}$$

where $$N_{k}$$ = [$$n_{1k}, n_{2k}, n_{3k}]$$ (column vector)

and where $$J_{k}^{-1}$$ is inverse of the

Jacobian matrix (3 x 3), $$J_{k}$$...

$$J_{k} = \frac{\partial(n_{1k}, n_{2k}, n_{3k})}{\partial(x_{k}, y_{k}, z_{k})} = \begin {bmatrix} 0 & 3(42-n_{2k})^{2/3}&3(42-n_{3k})^{2/3}\\ 3(42-n_{1k})^{2/3} & 0 &3(42-n_{3k})^{2/3}\\ 3(42-n_{1k})^{2/3} &3(42-n_{2k})^{2/3}& 0 \end{bmatrix}$$...
Guest

### Re: Is 42 a sum of three cubes?

We recall our previous equations:

E. $$x^{3} + y^{3} + z^{3} = 42$$;

$$n_{1k} = y_{k}^{3} + z_{k}^{3}$$;

$$n_{2k} = x_{k}^{3}+ z_{k}^{3}$$;

$$n_{3k} = x_{k}^{3}+ y_{k}^{3}$$;

$$x_{k}= (42 - n_{1k})^{1/3}$$;

$$y_{k}= (42 - n_{2k})^{1/3}$$;

$$z_{k}= (42 - n_{3k})^{1/3}$$.

Therefore, we derive the following equations:

$$\frac{\partial n_{1k} }{\partial x_{k} }= 0$$;

$$\frac{\partial n_{1k} }{\partial y_{k} }= 3y_{k}^{2}= 3(42-n_{2k})^{2/3}$$;

$$\frac{\partial n_{1k} }{\partial z_{k} }= 3z_{k}^{2}= 3(42-n_{3k })^{2/3}$$...
Guest

### Re: Is 42 a sum of three cubes?

$$N_{k+1} = N_{k} +J_{k}^{-1} * N_{k}$$

where $$N_{k}$$ = [$$n_{1k}, n_{2k}, n_{3k}]$$ (column vector)

and where $$J_{k}^{-1}$$ is inverse of the

Jacobian matrix (3 x 3), $$J_{k}$$.

$$J_{k}^{-1} = \begin {bmatrix} -(42-n_{1k})^{-2/3}/6 & (42-n_{1k})^{-2/3}/6&(42-n_{1k})^{-2/3}/6\\ (42-n_{2k})^{-2/3}/6&-(42-n_{2k})^{-2/3}/6&(42-n_{2k})^{-2/3}/6\\ (42-n_{3k})^{-2/3}/6&(42-n_{3k})^{-2/3}/6&(42-n_{3k})^{-2/3}/6 \end {bmatrix}$$.

Therefore,

$$N_{k+1} = \begin {bmatrix} n_{1k } + (42-n_{1k})^{-2/3}/6 * n_{1k } - (42-n_{1k})^{-2/3}/6 * n_{2k } - (42-n_{1k})^{-2/3}/6* n_{3k }\\ n_{2k } - (42-n_{2k})^{-2/3}/6 * n_{1k } + (42-n_{2k})^{-2/3}/6 * n_{2k } - (42-n_{2k})^{-2/3}/6* n_{3k }\\ n_{3k } - (42-n_{3k})^{-2/3}/6 * n_{1k } - (42-n_{3k})^{-2/3}/6 * n_{2k } + (42-n_{3k})^{-2/3}/6* n_{3k } \end {bmatrix}$$.
Guest

### Re: Is 42 a sum of three cubes? Please see above value for n_10:
MSP12742361766bfahghhb400004f2bi2g70bab6hf2.gif (2.86 KiB) Viewed 1122 times
Guest

### Re: Is 42 a sum of three cubes? Please see above value for n_20:
MSP310223defbda43b9g187000040fg7c30f9di6c0h.gif (2.86 KiB) Viewed 1122 times
Guest

### Re: Is 42 a sum of three cubes? Please see above value for n_30:
MSP243019hghe6224d4b25c00001625890ide000b25.gif (2.85 KiB) Viewed 1122 times
Guest

### Re: Is 42 a sum of three cubes?

$$N_{k+1} = N_{k} +J_{k}^{-1} * N_{k}$$

where $$N_{k}$$ = [$$n_{1k}, n_{2k}, n_{3k}]$$ (column vector)

and where $$J_{k}^{-1}$$ is inverse of the

Jacobian matrix (3 x 3), $$J_{k}$$.

$$J_{k}^{-1} = \begin {bmatrix} -(42-n_{1k})^{-2/3}/6 & (42-n_{1k})^{-2/3}/6&(42-n_{1k})^{-2/3}/6\\ (42-n_{2k})^{-2/3}/6&-(42-n_{2k})^{-2/3}/6&(42-n_{2k})^{-2/3}/6\\ (42-n_{3k})^{-2/3}/6&(42-n_{3k})^{-2/3}/6&(42-n_{3k})^{-2/3}/6 \end {bmatrix}$$.

Therefore,

$$N_{k+1} = \begin {bmatrix} n_{1k } + (42-n_{1k})^{-2/3}/6 * n_{1k } - (42-n_{1k})^{-2/3}/6 * n_{2k } - (42-n_{1k})^{-2/3}/6* n_{3k }\\ n_{2k } - (42-n_{2k})^{-2/3}/6 * n_{1k } + (42-n_{2k})^{-2/3}/6 * n_{2k } - (42-n_{2k})^{-2/3}/6* n_{3k }\\ n_{3k } - (42-n_{3k})^{-2/3}/6 * n_{1k } - (42-n_{3k})^{-2/3}/6 * n_{2k } + (42-n_{3k})^{-2/3}/6* n_{3k } \end {bmatrix}$$ = [$$n_{1k+1 }, n_{2k+1 }, n_{3k+1 }$$] (column vector).

We recall the following equations:

$$x_{k+1}= (42 - n_{1k+1})^{1/3}$$;

$$y_{k+1}= (42 - n_{2k+1})^{1/3}$$;

$$z_{k+1}= (42 - n_{3k+1})^{1/3}$$.
Guest

### Re: 42 a sum of three cubes?

Guest wrote:$$N_{k+1} = N_{k} +J_{k}^{-1} * N_{k}$$

where $$N_{k}$$ = [$$n_{1k}, n_{2k}, n_{3k}]$$ (column vector)

and where $$J_{k}^{-1}$$ is inverse of the

Jacobian matrix (3 x 3), $$J_{k}$$.

$$J_{k}^{-1} = \begin {bmatrix} -(42-n_{1k})^{-2/3}/6 & (42-n_{1k})^{-2/3}/6&(42-n_{1k})^{-2/3}/6\\ (42-n_{2k})^{-2/3}/6&-(42-n_{2k})^{-2/3}/6&(42-n_{2k})^{-2/3}/6\\ (42-n_{3k})^{-2/3}/6&(42-n_{3k})^{-2/3}/6&(42-n_{3k})^{-2/3}/6 \end {bmatrix}$$.

Therefore,

$$N_{k+1} = \begin {bmatrix} n_{1k } + (42-n_{1k})^{-2/3}/6 * n_{1k } - (42-n_{1k})^{-2/3}/6 * n_{2k } - (42-n_{1k})^{-2/3}/6* n_{3k }\\ n_{2k } - (42-n_{2k})^{-2/3}/6 * n_{1k } + (42-n_{2k})^{-2/3}/6 * n_{2k } - (42-n_{2k})^{-2/3}/6* n_{3k }\\ n_{3k } - (42-n_{3k})^{-2/3}/6 * n_{1k } - (42-n_{3k})^{-2/3}/6 * n_{2k } + (42-n_{3k})^{-2/3}/6* n_{3k } \end {bmatrix}$$ = [$$n_{1k+1 }, n_{2k+1 }, n_{3k+1 }$$] (column vector).

We recall the following equations:

$$x_{k+1}= (42 - n_{1k+1})^{1/3}$$;

$$y_{k+1}= (42 - n_{2k+1})^{1/3}$$;

$$z_{k+1}= (42 - n_{3k+1})^{1/3}$$.

For what integers, $$k, x_{k }, y_{k }$$, and $$z_{k}$$,

does $$x_{k}^{3} + y_{k}^{3}+ z_{k}^{3} = 42$$

when $$k \ge 0$$?
Guest

### Re: 42 a sum of three cubes?

Guest wrote:
Guest wrote:$$N_{k+1} = N_{k} +J_{k}^{-1} * N_{k}$$

where $$N_{k}$$ = [$$n_{1k}, n_{2k}, n_{3k}]$$ (column vector)

and where $$J_{k}^{-1}$$ is inverse of the

Jacobian matrix (3 x 3), $$J_{k}$$.

$$J_{k}^{-1} = \begin {bmatrix} -(42-n_{1k})^{-2/3}/6 & (42-n_{1k})^{-2/3}/6&(42-n_{1k})^{-2/3}/6\\ (42-n_{2k})^{-2/3}/6&-(42-n_{2k})^{-2/3}/6&(42-n_{2k})^{-2/3}/6\\ (42-n_{3k})^{-2/3}/6&(42-n_{3k})^{-2/3}/6&(42-n_{3k})^{-2/3}/6 \end {bmatrix}$$.

Therefore,

$$N_{k+1} = \begin {bmatrix} n_{1k } + (42-n_{1k})^{-2/3}/6 * n_{1k } - (42-n_{1k})^{-2/3}/6 * n_{2k } - (42-n_{1k})^{-2/3}/6* n_{3k }\\ n_{2k } - (42-n_{2k})^{-2/3}/6 * n_{1k } + (42-n_{2k})^{-2/3}/6 * n_{2k } - (42-n_{2k})^{-2/3}/6* n_{3k }\\ n_{3k } - (42-n_{3k})^{-2/3}/6 * n_{1k } - (42-n_{3k})^{-2/3}/6 * n_{2k } + (42-n_{3k})^{-2/3}/6* n_{3k } \end {bmatrix}$$ = [$$n_{1k+1 }, n_{2k+1 }, n_{3k+1 }$$] (column vector).

We recall the following equations:

$$x_{k+1}= (42 - n_{1k+1})^{1/3}$$;

$$y_{k+1}= (42 - n_{2k+1})^{1/3}$$;

$$z_{k+1}= (42 - n_{3k+1})^{1/3}$$.

For what integers, $$k, x_{k }, y_{k }$$, and $$z_{k}$$,

does $$x_{k}^{3} + y_{k}^{3}+ z_{k}^{3} = 42$$

when $$k \ge 0$$?

Keywords:. David Hilbert's Tenth Problem

Hmm. We may need a supercomputer to solve our problem. And there could be no solutions (doubtful) or there could be a few solutions (or at least one solution) or there could be infinitely many solutions too. Hmm. ??? We need a sound theory to explain any result... Does our search have a happy ending (at least one solution) or does it become an endless search according to the MRDP Theorem?

https://en.m.wikipedia.org/wiki/Diophantine_set

Dave.
Guest

### Re: Is 42 a sum of three cubes?

FYI: 'New sums of three cubes':

"Introduction. It is a long standing problem whether every rational integer
n ≡! 4, 5 (mod 9) may be written as a sum of three integral cubes. According to
the web page http://cr.yp.to/threecubes.html of Daniel Bernstein, the first attacks by computer were carried out as early as in 1955..."

Please see attachment for more details.
Attachments elk_ants6c.pdf
(73.94 KiB) Downloaded 49 times
Guest

Guest

### Re: Is 42 a sum of three cubes?

For the given problem, how do we adapt the Newton Method to find integral solutions (assuming their existence) as fast as possible?
Guest

Next

Return to Number Theory

### Who is online

Users browsing this forum: No registered users and 1 guest